Effect of grain refinement induced by wire and arc additive manufacture (WAAM) on the corrosion behaviors of AZ31 magnesium alloy in NaCl solution - Jianwei LI; Youmin QIU; Junjie YANG; Yinying SHENG; Yanliang YI; Xun ZENG; Lianxi CHEN; Fengliang YIN; Jiangzhou SU; Tiejun ZHANG; Xin TONG; Bin GUO (Journal of Magnesium and Alloys, 2023)
Additive manufacturing (AM) of Mg alloys has become a promising strategy for producing complex structures, but the corrosion performance of AM Mg components remains unexploited. In this study, wire and arc additive manufacturing (WAAM) was employed to produce single AZ31 layer. The results revealed that the WAAM AZ31 was characterized by significant grain refinement with non-textured crystallographic orientation, similar phase composition and stabilized corrosion performance comparing to the cast AZ31. These varied corrosion behaviors were principally ascribed to the size of grain, where cast AZ31 and WAAM AZ31 were featured by micro galvanic corrosion and intergranular corrosion, respectively.